Liberation psychology: a constructive critical praxis - Mark Burton (Estudos de Psicologia (Campinas))
Can a critical psychology be more than an inward looking critique of the discipline itself? Liberation psychology emerged in Latin America in the 1980s. It is a critical psychology with an action focus, taking sides with the oppressed populations of the continent. The originator of the approach, Ignacio Martín-Baró practiced psychology in the context of the El Salvador an civil war, himself becoming a victim of State repression. The consequences of social conflict have since then been an important theme for liberation psychology. Other areas of emphasis have been community social psychology with an emphasis on the role of social movements and social and political commentary and critique. I will present a review of the field covering some key concepts (conscientisation, de-ideologization, historical memory, reconstruction of psychology from the perspective of the other), its geographical spread (in Latin America and other regions), its organization (the emergence of liberation psychology networks and collectives) and some examples of work that is relevant to social trauma, the theme of this symposium.